UNDERSTANDING HADITH ABOUT FEMALE CIRCUMCISION: An Attempt to Reconstruct the Practice of Female Circumcision in Indonesia - Wijaya, Roma (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2023)
This article describes the problems of female circumcision or known as Female Genital Cutting/Mutilation (FGC/M). Pros and cons have sprung up regarding the legality of the practice of female circumcision in Indonesia, the pros are based on tradition, culture, and religious narratives, such as the hadith narrated by Abu Dawud. The contra group indicated negative effects on women from a health perspective, such as genital ulceration, injuries to nearby tissues, septicemia and even death due to bleeding. Therefore, this research actualizes the understanding regarding female circumcision by looking at various aspects. This research is a qualitative type of library research using a descriptive-analytical method. The approach used is ma’anil hadis to see the explanation, description of female circumcision, then actualized in the current context in Indonesia. The results of this study are first, the hadith of female circumcision contained in Sunan Abu Daud is dhaif, munkar, even ma’lul/problematic. Second, female circumcision does not need to be carried out on the grounds that WHO has disclosed the complications caused by circumcision. Strengthened by regulations from the Indonesian Ministry of Health, Islamic mass organizations, as well as other figures such as Husein Muhammad.[Artikel ini menjelaskan problematika khitan perempuan atau disebut sebagai Female Genital Cutting/Mutilation (FGC/M). Pro kontra bermunculan mengenai legalitas praktek khitan perempuan di Indonesia, kalangan pro berasaskan pada tradisi, budaya, serta narasi-narasi agama. Kelompok kontra mengindikasikan adanya efek negatif terhadap perempuan dari segi Kesehatan seperti ulserasi alat kelamin, luka pada jaringan terdekat, septikemia bahkan kematian akibat pendarahan. Sebagaimana hadis| yang diriwayatkan oleh Abu Dawud. Hadis ini dinilai da’if karena ada sanad bernama Muhammad bin Hassan berstatus Majhul. Namun, pada praktiknya masih saja diamalkan oleh masyarakat Indonesia. Oleh karena itu, penelitian ini berupaya merekontruksi pemahaman terkait khitan perempuan dengan melihat berbagai aspek. Penelitian ini kualitatif yang berjenis library research dengan menggunakan metode deskripsi-analitis. Pendekatan yang digunakan adalah ma’anil hadis untuk melihat penjelasan, gambaran tentang khitan perempuan, kemudian diaktualisasikan pada konteks saat ini di Indonesia. Hasil penelitian ini adalah pertama, hadis khitan perempuan yang terkandung dalam Sunan Abu Daud bernilai dhaif, munkar, bahkan ma’lul/bermasalah. Kedua, khitan perempuan tidak perlu dilaksanakan dengan alasan WHO telah mengungkapkan komplikasi yang ditimbulkan oleh khitan. Diperkuat dengan peraturan Kementerian Kesehatan RI, ormas-ormas Islam, serta tokoh lain seperti Husein Muhammad.]